Peluang Dan Tantangan Wisata Medis Indonesia Terkait Undang-Undang Kesehatan Baru 2023 - Janetty (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Medical tourism destinations involve intentional travel by patients to privately receive medical treatment in another country. Empirical evidence regarding the health and safety risks faced by medical tourists is limited. In Indonesia, the ratification of the new 2023 Health Law has been carried out and the contents of the law are related to medical tourism, one of which is the regulation of medical personnel and foreign health workers in Indonesia. Of course, this medical tourism still requires improvement from Indonesia's own health system so that it can be carried out properly. The research method of this paper uses library research by examining the 2023 Health Law and its relation to medical tourism. The results obtained are opportunities in the form of increasing the economy from organizing medical tourism in Indonesia, as well as challenges in the form of improving the quality and equity of access to health facilities in Indonesia and competition between foreign and local medical and health personnel. Opportunities and challenges related to medical tourism, along with some recommendations to related parties, especially the Government through the Ministry of Tourism to make policies that are more comprehensive in making medical tourism a sustainable sector.